Assessment of comorbidities in patients with deranged thyroid hormone levels - Narwade, Sneha D.; Barve, Rohidas M. (International Journal of Basic & Clinical Pharmacology, 2020)
Background: There is association of deranged thyroid hormone levels with various co-morbidities. Drugs for comorbidity may interact with each other and affect the outcome of treatment. So, this study was planned to find out comorbidities with deranged thyroid hormone levels and various possible drug interactions. Methods: It was a prospective, observational study carried out at tertiary care hospital from November 2017 to June 2018. Thyroid hormonal levels reports were followed in OPD and online information system facility. Drugs interactions were checked by referring standard pharmacology textbooks, review articles and Medscape drug interaction checker. Approval from the Institutional Ethics Committee was taken before initiation of the study. Patients with deranged thyroid hormone levels were included in the study. Results: Study was conducted in 111 patients of thyroid disorders. Spondylitis, asthma, acne cases were seen in hypothyroid patients whereas hypokalemic periodic paralysis, thyroid ophthalmopathy statistically significantly seen in hyperthyroid patients. Various concurrent medications such as calcium, carbamazepine decreases the effects of levothyroxine. For management of comorbidities various drugs are given which also interact among themselves significantly. Conclusions: Diabetes mellites, obesity, spondylitis, lichen planus were more common in hypothyroidism while comorbidities like hypertension, hypokalemic periodic paralysis, thyroid ophthalmopathy were found to be more in hyperthyroidism. Incidence of drug interactions is found to be more with increased use of medications for comorbidities, so physicians should be careful while prescribing them. Due to drug interactions desired effects of drugs given for thyroid disorders may not be observed.